2021
DOI: 10.1021/acsaem.1c00452
|View full text |Cite
|
Sign up to set email alerts
|

Self-Standing, Robust Membranes Made of Cellulose Nanocrystals (CNCs) and a Protic Ionic Liquid: Toward Sustainable Electrolytes for Fuel Cells

Abstract: Energy-conversion devices based on the phenomenon of proton conduction, for example, polymer electrolyte membrane fuel cells (PEMFCs), require low cost and sustainable electrolytes with high ionic conductivity and good mechanical properties under anhydrous conditions and at temperatures up to 150 °C. Biopolymers possess an intrinsic thermomechanical stability but an insufficient proton conductivity in the dry state, which however may be imparted by a protic ionic liquid (PIL). This work presents the preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Aprotic ionic liquids (APILs) to prepare these materials are used. , We believe using PILs instead of APILs will be a better solution to obtain electrolytes showing high proton conductivity because PILs have exchangeable, mobile protons. Danyliv et al reported the first results for CNC-based composites with PILs. The composites showed good thermal stability up to 200 °C and conductivity values from 10 –2 to 10 –1 S/m under anhydrous conditions in the range of 120–160 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Aprotic ionic liquids (APILs) to prepare these materials are used. , We believe using PILs instead of APILs will be a better solution to obtain electrolytes showing high proton conductivity because PILs have exchangeable, mobile protons. Danyliv et al reported the first results for CNC-based composites with PILs. The composites showed good thermal stability up to 200 °C and conductivity values from 10 –2 to 10 –1 S/m under anhydrous conditions in the range of 120–160 °C.…”
Section: Introductionmentioning
confidence: 99%
“…20 The possibility to obtain a selfstanding and robust membrane even of the rigid CNCs in combination with an IL was demonstrated by Danyliv et al, who used such a membrane as a fuel cell polymer electrolyte. 21 To the best of our knowledge, gas permeation studies have not been conducted on CNC/IL blends.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A CNF film plasticized by the ionic liquid (IL) 1-ethyl-3methylimidazolium acetate showed excellent CO 2 selectivities and good permeability at the same time, illustrating the potential of such blends . The possibility to obtain a self-standing and robust membrane even of the rigid CNCs in combination with an IL was demonstrated by Danyliv et al, who used such a membrane as a fuel cell polymer electrolyte . To the best of our knowledge, gas permeation studies have not been conducted on CNC/IL blends.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, continuous research efforts have been made to develop cost-effective and eco-friendly PEMFCs from renewable sources. Natural-based polymers such as chitosan, alginate, carrageenan, starch, or cellulose are being investigated as “green” materials for fuel cells, owing to their biodegradability, nontoxicity, and low-cost. With the significant exception of cellulose, most of these biopolymers (e.g., the widely reported chitosan or carrageenan) exhibit high water solubility and low mechanical strength, obvious handicaps for their application in PEMFCs. An even greater handicap is the low ionic conductivity of these biopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…An even greater handicap is the low ionic conductivity of these biopolymers. Among various strategies to improve the conductivity of these host biopolymers, the combination with a conducting ionic liquid (IL) into composite membranes has attracted considerable attention in the last years. However, the application of these composites in fuel cells is still limited due to the losses of the unbound IL during cell operation …”
Section: Introductionmentioning
confidence: 99%